Electrical and Thermal study of carbon nanotubes reinforced poly (phenylene sulfide) nanostructured composites - Ribeiro, Bruno [UNESP] (2015)
In this work, the crystallization behavior and electrical conductivity of multiwalled carbon nanotubes reinforced poly (phenylene sulfide) nanostructured composites obtained by melt mixing were investigated. The incorporation of nanofiller in polymeric matrix was responsible for an increase in crystallinity due heterogeneous nucleation phenomenon. The electrical conductivity of PPS showed an increase by 11 orders of magnitude when 2.0 wt% of MWCNT was considered. Moreover, the electrical percolation threshold found on this system was 1.4 wt%, suggesting the formation of three-dimensional conductive network within the polymeric matrix.